Chemical composition of gahnite and degree of pegmatitic fractionation in the Borborema Pegmatitic Province, northeastern Brazil - Soares,Dwight R. (2007)
Gahnite electron probe microanalyses from three pegmatites (Mirador, Capoeira and Quintos) of the Borborema Pegmatitic Province in northeastern Brazil allowed to determine molar compositions ranging from 86.22 to 95.41 mol% gahnite (ZnAl2O4), 1.51 to 6.62 mol% hercynite (Fe2+Al2O4), 0.11 to 5.89 mol% spinel (MgAl2O4), 1.48 to 2.74 mol% galaxite (MnAl2O4), and Zn/FeTotal atomic ratios ranging from 11.53 to 60.87. These data compared with gahnite compositions from albite subtype pegmatites from Cap de Creus, Spain (Zn/FeTotal between 10 and 60) and from the source granite of the Separation Rapids pegmatite field, Ontario, Canada (Zn/FeTotal =3.5) indicate a high degree of fractionation of the studied pegmatites. This interpretation agrees with conclusions based on compositional data of tourmaline (vacancy in X-site 0.42 to 0.49), white mica (K/Rb between 8 and 33), feldspar (K/Rb between 8 and 109), garnet (Mn/(Mn+Fe2+)between 0.93 and 0.97) and in Nb-Ta oxides (Mn/(Mn+Fe2+)>0.5) in the same pegmatites.